Chironomid midges from early Eocene amber of France (Diptera: Chironomidae) - Doitteau, Gaelle; Nel, André (Zootaxa, 2007)
The Basal Eocene Oise amber has provided a rich and diverse chironomid fauna of 30 recognised species, with a general taxonomic pattern similar to that of the modern fauna. Among these fossils, 19 species are described in 17 recent genera, and 7 are attributed to 6 extinct new genera; thus, only 22% of the genera are not recent. All species belong to recent subfamilies, and the great majority to recent genera. We provide paleoenvironmental and paleoclimatic inferences, based on analyses at both the subfamily and generic levels. The subfamily analysis was conducted with 841 specimens, and revealed 14.9% Tanypodinae, 23.7% Chironominae, 0.4% Prodiamesinae, 0.3% Diamesinae, and 60.3% Orthocladiinae. The Chironominae are a minority in this fauna, but probably not because of climatic constraints. This subfamily was probably absent in the Upper Cretaceous and still under diversification during the Early Paleogene. Our generic inferences are congruent with available palaeoclimatic and palaeoecological reconstructions. They provide an image of a sandy, backwater fluvial deposit under a warm climate.